Optimalisasi Manajemen Masjid Nurul Iman Dalam Meningkatkan Kegiatan Keagamaan Bagi Masyarakat Di Desa Manggar Raya Kecamatan Tanjung Lago Kabupaten Banyuasin - Sutry Noer Aini; Hidayatullah (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Analysis of Suluk as a Da'wah Method in Increasing Religious Understanding for Followers of the Naqsbandiyah Tarekat at the Kiai Marogan Islamic Boarding School in Palembang." The aim of this research is to find out and analyze suluk as a da'wah method in increasing religious understanding for Naqsbandiyah Tarekat followers at the Kiai Marogan Islamic boarding school Palembang. This type of research is field research with a qualitative descriptive approach. Data collection techniques in this research are observation, interviews and documentation. This data analysis technique is descriptive qualitative through three stages, namely data reduction, data presentation, conclusions and verification. This research data uses the theory of da'wah methods popularized by Moh. Ali Aziz and the Theory of Understanding Religion which was popularized by R. Stark and C. Y. Glock. The results of this research are that Suluk, which is practiced by the Naqsabandiyah Tarekat at the Kiai Marogan Islamic Boarding School in Palembang, is used as part of the da'wah method. The theory is the lecture method, discussion method, counseling method, written work method, community development method and institutional method. Of these several methods, there is one method of da'wah that is not in suluk, namely the discussion method. Understanding of religion for followers of the Naqsabandiyah Tarekat at the Kiai Marogan Islamic boarding school in Palembang. In this research there are several theories. The theory of understanding religion is the dimension of belief, the dimension of religious practice, the dimension of experience, the dimension of religious knowledge and the dimension of consequences.